The teaching of vocal agility in todays pedagogic of singing - Zelenkova, Dagmar (Aura musica, 2012)
Today's vocal pedagogic has its base in the principles of belcanto which is based on the technical principles of singing in the 18th and first half of th 19th century. Using the exercises of the vocal techniques of the authors of belcanto as an illustrive application the perfect agility of the voice can also be achieved today.
Keywords: agility of the voice; martellato; technique of the passages; ideal of belcanto